Banks, Credit Reallocation, and Creative Destruction - Christian Keuschnigg; Michael Kogler; Johannes Matt (Center for Economic Studies and ifo Institute (CESifo), 2022)
How do banks facilitate creative destruction and shape firm turnover? We develop a dynamic general equilibrium model of bank credit reallocation with endogenous firm entry and exit that allows for both theoretical and quantitative analysis. By restructuring loans to firms with poor prospects and high default risk, banks not only accelerate the exit of unproductive firms but also redirect existing credit to more productive entrants. This reduces banks' dependence on household deposits that are often supplied inelastically, thereby relaxing the economy's resource constraint. A more efficient loan restructuring process thus fosters firm creation and improves aggregate productivity. It also complements policies that stimulate firm entry (e.g., R&D subsidies) and renders them more effective by avoiding a crowding-out via a higher interest rate.
Keywords: E23; E44; G21; O40; 330; creative destruction; reallocation; bank credit; productivity